Lactobacillus delbrueckii might lower serum triglyceride levels via colonic microbiota modulation and SCFA-mediated fat metabolism in parenteral tissues of growing-finishing pigs - Hou, Gaifeng; Yin, Jie; Wei, Liangkai; Li, Rui; Peng, Wei; Yuan, Yong; Huang, Xingguo; Yin, Yulong (Frontiers in Veterinary Science, 2022)
Gut microbiota and its metabolites play a key role in host metabolism. Our previous study found supplemental Lactobacillus delbrueckii affected lipid metabolism of pigs, however, the underlying mechanism is unclear. In this study, we investigated the effects of Lactobacillus delbrueckii on colonic bacteria composition and its metabolites, serum lipids and hormone levels, fat metabolism related enzyme activity and gene expression in various tissues of growing-finishing pigs. Twelve pigs were randomly distributed into two groups (n=6), and pigs in each group were fed diets with (Con + LD) or without (Con) 0.1 % Lactobacillus delbrueckii for 28 days. Results exhibited the deceased triglyceride (TG) levels and elevated free fatty acid (FFA) contents in serum and increased concentrations of butyric acid in colonic digesta after Lactobacillus delbrueckii supplementation. Dietary Lactobacillus delbrueckii increased abundance of Lactobacillus and Butyrivibri and tended to increase abundance of Akkermansia and Megasphaera in colonic digesta. Lactobacillus delbrueckii consumption up-regulated glucagon-like peptide1 (GLP-1), monocarboxylate transporter1 (MTC1) and sodium-dependent monocarboxylate transporter1 (SMCT1) expression in colonic tissue. Administration of Lactobacillus delbrueckii tended to increase lipoprotein lipase (LPL) activity, up-regulated CPT-1, angiopoietin-like protein 4 (Angpt14), LPL and triglyceride hydrolase (TGH) expression and down-regulated fatty acid synthetase (FAS), G protein-coupled receptor 41(GPR41) and GPR43 expression in the liver. Lactobacillus delbrueckii addition increased adenosine monophosphate activated protein kinase (AMPK) expression in longissimus dorsi, upregulated LPL, CPT-1, Angptl4 and cluster of differentiation 36 (CD36) expression in subcutaneous fat, and enhanced LPL, CPT-1, TGH, adipocyte determination and differentiation-dependent factor 1 (ADD1) and hormone sensitive lipase (HSL) expression in leaf lard. These findings suggested that Lactobacillus delbrueckii might enhance lipolysis and fatty acid β-oxidation to lower serum TG levels via colonic microbiota modulation and short chain fatty acids-mediated lipid metabolism of growing-finishing pigs.